Incidência e fatores de risco para sífilis e gonorreia em uma coorte de homossexuais e bissexuais masculinos HIV negativos, Projeto Horizonte, 1994 - 2010 - Jaqueline Maria Calazans (2013)
Background: Project Horizonte is an open cohort study of homosexual/bisexual HIV negative men, established in 1994 and coordinated by the Federal University of Minas Gerais, Belo Horizonte, MG. Its objectives included to evaluate HIV incidence and others STDs, to investigate risk factors for infection, to evaluate preventive measures and to assess the volunteers willingness to participate in HIV vaccine trials. Volunteers are monitored every six months through interviews psychosocial, medical and laboratory exams. In Brazil, epidemiological data regarding STDs are scarce and until 2010 only AIDS, HIV in pregnancy/child exposed, syphilis in pregnancy and congenital syphilis were of compulsory reportable diseases. Acquired syphilis became a reportable disease only in Sep tember, 2010. Objective: The aim of this study was to evaluate the incidence and risk factors associated with syphilis and gonorrhea among volunteers followed in Project Horizonte from 1994-2010. Methods: The information used in the present study was collected from clinical and psychosocial questionnaires applied semiannually. Variables analyzed included socio demographic characteristics, sexual behavior, risk factors for syphilis and gonorrhea. The events of interest were incident cases of syphilis and gonorrhea during the follow-up. The overall incidence rates and incidence rates by admission periods (1994-1999, 2000-2004, 2005-2010) were estimated per 100 person-years, by each disease. Multivariate Cox proportional hazard models were performed to investigate the risk factor associated with syphilis and gonorrhea. Results: From 1994 to 2010, 1091 volunteers were recruited. The majority (62.2%) were aged between 21 and 30 years to join the cohort; 50,3% of the volunteers had more than eight years of education, 62,6% had income between 1 and 3 minimum wages and 37,0%, income greater than 3 times the minimum wage; predominance of single individuals (94,9%) and only 6,9% had children, 20,1% were bisexual behavior. During the follow-up time, were found 94 syphilis incident cases (3,5/1000 persons -year; 95% CI 2.8-4.3). Incidence rates by period were 2,86, 3,95 e 4,86 by 100 persons -year. The main risk factors associated with syphilis infection were be young (HR: 0.97, 95%CI: 0.94-0.99) and having sex with partner with STDs in the last 6 months (HR: 2.12, 95%CI: 1.10 -4.11). In addition, were found 20 gonorrhea incident cases (0.95/100 person-years, 95%CI 0.6-1.5). Incidence rates by period were 0.78, 1.15 and 1.17 by 100 person-years. The risk factors associated with gonorrhea were be young (HR: 0.93, 95%CI, 0.87 -0.99) and search sexual partners in sauna, in the last 6 months (HR: 2.65, 95%CI, 1.08 - 6.50). Conclusions: The incidence rates of syphilis and gonorrhea have increased over time. The younger volunteers, those who search sexual partners in saunas and had sexual partners with STD, had higher risk for syphilis and gonorrhea. Despite the volunteers have information about STD, high level of counseling and condom distribution during the follow-up a proportion of them continues to engage in high risk practices. Therefore, it is necessary to better investigate the individual and social aspects that interfere with unsafe sexual practices.